A Conceptual Model for Nurses' Decision-making with the Aggressive Psychiatric Patient. (3rd August 2015) - Moylan, Lois Biggin
Abstract : Violence in the acute care psychiatric setting is an ongoing serious problem. Maintenance of a safe therapeutic environment is a paramount responsibility of nurses practicing in this area. Ethical and legal standards demand that the nurse intervenes in aggressive situations in a manner that employs the least intrusive and restrictive measures necessary to provide safety. Therefore, accurate and effective decision-making in aggressive situations, which can escalate rapidly, is of great importance. This paper discusses a theoretical model for decision-making in selecting interventions with aggressive psychiatric patients. This model may provide a basis for the development of training and education programs for effective decision-making in this area.